Enamel and dentin dust as skin irritants - Francisco, Dennis Z.
Dental students of four different colleges namely Centro Escolar University, University of the East, Unciano Paramedical College, and the University of the Philippines were patched tested using contaminated and sterile enamel and dentin dust to determine if there is skin irritation among allergic and non-allergic dental students in three different sites namely the face, arm and back. Results show that a) there is more severe skin irritation with contaminated enamel and dentin dust than sterile dust; b) a history of allergy predisposes the individual's chances of developing manifestations of skin irritation more than those without allergy; c) that there is a decreasing order of susceptibility to skin irritation in three different sites namely the face, arm and the back in that order.